ANALISIS PERENCANAAN KEBUTUHAN BAHAN BAKU DENGAN METODE MRP PADA PT BOGOR MITRADAYA MANDIRI - Dewi Taurusyanti; Feri Anggara Putra (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2018)
Raw material requirements planning is one way to increase cost efficiency. The purpose of this study wasto determine the proper technique for cost efficiency. The Research in Bogor Mitradaya PT Mandirifacing problems of shortage or excess raw materials in the warehouse or stock outs so disrupt the smoothproduction process. Comparative descriptive research with case study method. The analysis wasconducted using MRP (Material Requirement Planning). The Results showed that raw materialrequirements planning at PT Mandiri Bogor Mitradaya pretty good. But in its activities, sometimescompanies have excess or shortage of raw materials warehouse, causing inefficient costs on 17th feb-23feb 2015. The calculation methods Lot For Lot MRP techniques proven to increase cost efficiency. Thus,the authors recommend techniques Lot For Lot to be considered, especially in decision making.